1998
DOI: 10.1002/(sici)1096-9071(199811)56:3<230::aid-jmv9>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and genotypes in Southern Israel and the Gaza strip

Abstract: The Gaza Strip borders the southern part of Israel and Egypt. There is a remarkable difference in the prevalence of antibodies to hepatitis C virus (HCV) between Israel (0.5%) and Egypt (10%). A few thousand inhabitants cross the borders daily from the Gaza Strip to both countries. The objectives of this study were to investigate the prevalence of HCV infection in the Gaza Strip, an area that was not studied before, and to study HCV transmission in the Gaza Strip by characterizing the genotypes of HCV in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
5
24
0
Order By: Relevance
“…The exceptional occurrence of genotype 4 in southern Turkey is in favor of such a hypothesis. This particular genotype is endemic in Egypt and highly prevalent in the other Middle East countries with the exception of Israel [8,9]. It appears that the genotype 4 did not propagate from these countries towards Turkey.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The exceptional occurrence of genotype 4 in southern Turkey is in favor of such a hypothesis. This particular genotype is endemic in Egypt and highly prevalent in the other Middle East countries with the exception of Israel [8,9]. It appears that the genotype 4 did not propagate from these countries towards Turkey.…”
Section: Discussionmentioning
confidence: 93%
“…In Egypt, Hepatitis C is an endemic disease that is associated with genotype 4, almost exclusively [8]. Similarly, genotype 4 is also predominant in the Gaza region, but not in Israel where subtype 1b is predominant [9]. The distribution of HCV genotypes in liver disease patients living in Syria, Iraq and Iran is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the published literature, the seroprevalence of HCV infection in Iranian general population is lower compared to other countries in the Middle East region. The general population-based studies that have assessed the prevalence of HCV infection in the middleeast countries include two studies from Turkey with the reported seroprevalence of 1% and 2.1% (21,22), a study from the Gaza strip with the reported seroprevalence of 2.2% (23), and a systematic review study from Yemen with the reported seroprevalence of 1.7% (24). Based on expert consensus, the seroprevalence of HCV infection is estimated to be 1.5% among United Arab Emirates general population (3).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of HCV genotype in Jordan differed from the other Arab countries, predominantly genotype 1a (40%), followed by genotype 1b (33%) and genotype 4 (33.3%) [60] . The most common genotype in Southern Israel was genotype 1b (62%) while genotype 4 (78%) was predominant in the Gaza Strip [61] . Turkey serves as a bridge between Europe and Asia, and HCV genotype pattern is similar to Eastern and Southern European countries, having genotype 1b as the most frequent genotype (> 70%) followed by genotype 1a [62] .…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%